the Role of Youth and Social Movements in the Digital Age: A Study of Activist Groups, the Use of Technology in Political Expression, and its Impact on Thai Society - Delokrattanakul ์Nudtera (Thai Social Science Journal, 2026)
This article analyzes the role of youth and social movements in the digital era, focusing on the study of youth activists in Thailand and their use of digital technologies as tools for political expression and communication. The movements in this era are characterized by the utilization of social media platforms and online technologies that provide youth with broad and rapid access to social and political issues. The article examines the impact of these movements on Thai society, including increased political participation among youth, shifts in political attitudes and culture, as well as challenges arising from the use of digital technologies, such as misinformation, censorship, and online privacy concerns. These challenges require careful management to promote effective and sustainable activism. Furthermore, the article proposes policy recommendations to support responsible technology use, enhance youth media literacy, and create safe spaces for political expression and participation in the digital age. These proposals aim to strengthen the role of youth in driving Thai society toward genuine equality and freedom.